Audit of a nurse endoscopist based one stop dyspepsia clinic. Issue 917 (1st March 2002) - Melleney, E M-A; Willoughby, C P
Abstract : As a response to the UK Health Department's "two week cancer wait" initiative a one stop dyspepsia clinic based on a nurse endoscopist was introduced, and the first 100 cases attending this clinic have been audited. After referral on a purpose designed form, patients were assessed by a gastroenterologist and then investigated at the same visit—where possible and appropriate—by endoscopy or ultrasound scan. All endoscopies were performed by a trained nurse specialist. Of the 100 patients, 84 were gastroscoped the same day and 11 had an ultrasound scan. Inappropriate tests were avoided in 16% of referrals. The commonest endoscopic diagnoses were minor oesophageal or gastroduodenal inflammation (64% of gastroscopies). Only six oesophageal or gastric cancers were found—all at an advanced stage—and three further malignancies were diagnosed. Only a minority (12%) of the patients with "alarm symptoms" had cancer. The waiting time for an appointment rose progressively during the first six months of the clinic. The system was popular with patients as most of them (70%) were dealt with at a single hospital attendance. Basing the endoscopy practice on a trained nurse specialist not only facilitated the creation of the service by maximising the use of scarce resources, but also improved communication and overall management of patients.